Preparation method and application of NiFeCr oxygen electrode based on nitrogen-containing organic ligand chelation
Patent Information
- Application Number
- CN202610893797.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-22
- Publication Date
- 2026-11-03
- Estimated Expiration
- 2046-06-22
AI Technical Summary
Existing NiFeCr-LDH catalysts are prone to chromium ion dissolution in alkaline electrolytes, leading to catalyst performance degradation and making it difficult to meet the long-term stable operation requirements of seawater electrolysis.
A method for preparing NiFeCr oxygen evolution electrode using nitrogen-containing organic ligand chelation was adopted. NiFeCr-MOF was grown in situ via a solvothermal method and transformed in situ into a N-doped NiFeCr-OOH oxygen evolution active phase during electrochemical activation, thereby achieving chromium fixation and enhanced catalytic activity.
It significantly improves the electrochemical activity and chlorine corrosion resistance of the catalyst, enhances the long-term operational stability of the electrode, and is suitable for seawater electrochemical oxygen desorption reaction.
Smart Images

Figure CN122406277B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the technical field of electrolytic oxygen evolution, and in particular to a method for preparing and applying a NiFeCr oxygen evolution electrode based on nitrogen-containing organic ligand chelation. Background Technology
[0002] In seawater electrolysis systems, compared to the cathode hydrogen evolution reaction (HER), the anodic oxygen evolution reaction (OER) requires a four-electron transfer process and has a higher energy barrier; simultaneously, seawater contains a large amount of chloride ions (Cl... - Oxygen evolution electrocatalysts (OECs) can compete with chlorine evolution reactions at the anode, causing severe corrosion to the anode catalyst and substrate, significantly impacting electrode activity and long-term durability. Therefore, developing non-precious metal OECs with both high activity and chlorine corrosion resistance has become a key research focus in seawater electrolysis for hydrogen production.
[0003] Among numerous catalytic systems, nickel-iron-based double hydroxides (NiFe-LDH) are widely considered promising catalytic materials in alkaline OER media due to their low cost and good electrocatalytic activity. Multi-metal doping of NiFe-LDH is a common method for effectively optimizing the electronic structure of the catalyst, improving its activity and corrosion resistance. Studies have shown that introducing chromium into NiFe-LDH can regulate the electronic structure of the metal sites, inhibit excessive oxidation of nickel sites, and form a chromium-containing protective layer on the catalyst surface, thereby improving stability in chlorinated electrolytes (Stabilizing NiFesites by high-dispersity of nanosized and anionic Cr species toward durable seawater oxidation. Nat. Commun. 2024, 15, 6624). However, existing NiFeCr-LDH catalysts are mostly prepared by electrodeposition or co-precipitation. When operating in alkaline electrolytes, chromium ions are easily dissolved and lost, leading to catalyst performance degradation and making it difficult to meet the long-term stable operation requirements of seawater electrolysis. Summary of the Invention
[0004] To address the aforementioned technical problems, this invention provides a method for preparing and applying a NiFeCr oxygen evolution electrode based on nitrogen-containing organic ligand chelation. The method utilizes the coordination and chelation effect of nitrogen-containing organic ligands to effectively fix chromium. NiFeCr-MOF is grown in situ using a solvothermal method, and during electrochemical activation, it is in situ transformed into a N-doped NiFeCr-OOH oxygen evolution active phase. This method can improve electrochemical activity and effective reaction area while inhibiting the dissolution of active components and enhancing resistance to chlorine corrosion, thus exhibiting excellent catalytic activity and long-term operational stability. It can be better applied to seawater electrochemical oxygen evolution reactions.
[0005] The objective of this invention is achieved through the following technical solution: This invention provides a method for preparing a NiFeCr oxygen evolution electrode based on nitrogen-containing organic ligand chelation, comprising the following steps: (1) A precursor solution is obtained by dissolving a nickel source, an iron source, a chromium source and a nitrogen-containing organic ligand in an organic solvent; the nitrogen-containing organic ligand is one or more of 2,2'-bipyridine-5,5'-dicarboxylic acid, 2,2'-bipyridine-4,4'-dicarboxylic acid, 2,5-pyridinedicarboxylic acid, tetracarboxyphenylporphyrin and 3,5-pyrazoledicarboxylic acid; (2) The pretreated conductive substrate is immersed in the precursor solution and subjected to a solvothermal reaction to obtain the NiFeCr-MOF precursor electrode; (3) The NiFeCr-MOF precursor electrode was placed in an alkaline electrolyte for electrochemical activation to obtain an N-doped NiFeCr oxygen evolution electrode.
[0006] This invention utilizes metal-organic framework (MOF) precursors to chelate functional metals and further convert them in situ into oxygen evolution reaction (OER) electrodes, thereby achieving efficient introduction and stable fixation of chromium in NiFe-based oxygen evolution electrocatalysts and obtaining highly active, corrosion-resistant, long-lasting seawater electrochemical oxygen evolution electrode materials.
[0007] Cr (Cr) readily dissolves or undergoes phase separation in strong bases and chlorine-containing systems. How to suppress Cr loss while maintaining catalytic activity has always been a technical challenge in this field. Utilizing Cr... 3+ Strong coordination affinity for nitrogen-containing organic ligands and the selection of nitrogen-containing organic ligands with specific structures can stabilize chromium through coordination chelation, effectively suppressing its dissolution in alkaline electrolytes. Through in-situ electrochemical activation, MOFs can undergo in-situ self-reconstruction, gradually transforming into an active phase dominated by NiOOH / FeOOH, while retaining stable chromium doping and N-doped structures derived from nitrogen-containing organic ligands. This self-reconstruction process not only avoids complex multi-step deposition and post-processing techniques but also constructs a catalyst layer with high electrochemical surface area and hierarchical porous structure, significantly increasing the electrochemical active area. Furthermore, the introduction of chromium and N doping helps to regulate the electronic structure of the active center of NiFe-based catalysts and enhances resistance to chlorine corrosion, potentially leading to highly active and stable non-noble metal OER anode electrodes.
[0008] Preferably, in step (1), the molar ratio of Ni, Fe, and Cr in the nickel source, iron source, and chromium source is 2-6:1-3:0.1-2; more preferably, the molar ratio of Ni, Fe, and Cr in the nickel source, iron source, and chromium source is 2-3:1-2:0.3-0.6.
[0009] Preferably, in step (1), the ratio of the total molar amount of metal ions to the molar amount of nitrogen-containing organic ligands in the precursor solution is 1:0.5-2.0; more preferably, the ratio of the total molar amount of metal ions to the molar amount of nitrogen-containing organic ligands in the precursor solution is 1:0.75-1.5.
[0010] Preferably, in step (1), the ratio of the total molar amount of metal ions to the molar amount of organic solvent in the precursor solution is 1:20-200; more preferably, the ratio of the total molar amount of metal ions to the molar amount of organic solvent is 1:60-150.
[0011] Preferably, in step (1), the nickel source, iron source and chromium source are one or more of nitrate, chloride, sulfate and acetate, respectively.
[0012] Preferably, in step (1), the organic solvent is one or more of N,N-dimethylformamide, N,N-dimethylacetamide, ethanol, methanol, isopropanol, dichloromethane, acetonitrile, and dimethyl sulfoxide.
[0013] Preferably, in step (2), the conductive substrate includes carbon paper, carbon cloth, or nickel foam.
[0014] Preferably, in step (2), the pretreatment of the conductive substrate includes the following steps: the conductive substrate is ultrasonically cleaned sequentially with an organic solvent and an acidic solution, then cleaned with water and an alcohol solvent and dried to obtain the pretreated conductive substrate.
[0015] Preferably, the organic solvent is one or more of acetone, ethanol, and isopropanol; the acidic solution is hydrochloric acid, nitric acid, or sulfuric acid, with a concentration of 0.1-3.0 mol·L⁻¹. -1 The ultrasonic cleaning time is 2-10 minutes.
[0016] Preferably, in step (2), the solvothermal reaction is carried out at 100-160℃ for 6-24 h.
[0017] Preferably, in step (3), the alkaline electrolyte is a 0.5-3 M KOH solution; the electrochemical activation is performed at a constant current density of 10-300 mA·cm⁻¹. -2 Activation time is 2-24 hours.
[0018] Secondly, the present invention also provides an application of the NiFeCr oxygen evolution electrode prepared by the above preparation method in the electrochemical oxygen evolution reaction in seawater or in the electrochemical oxygen evolution reaction in strongly alkaline seawater (pH≥10).
[0019] Compared to traditional NiFe-based oxygen evolution catalysts, the NiFeCr oxygen evolution electrode in this invention, when used as an anode in alkaline water electrolysis, seawater electrolysis, or strongly alkaline seawater electrolysis systems, exhibits excellent catalytic activity, structural stability, and resistance to chlorine corrosion.
[0020] Compared with the prior art, the present invention has the following beneficial effects: (1) By coordinating and chelating chromium with nitrogen-containing organic ligands, the uniform introduction and stable fixation of chromium in NiFe-MOF precursor were achieved, which effectively avoided the problem of easy dissolution of chromium components in alkaline electrolysis reaction in traditional electrodeposition or coprecipitation methods, and improved the structural stability of the multi-metal synergistic catalytic system. (2) A structurally stable NiFeCr-based oxygen evolution electrode was constructed by in-situ growth of MOF on a conductive substrate and its self-reconstruction during electrochemical activation. Under oxygen evolution reaction conditions, the electrode can be transformed from MOF in situ into an active phase mainly composed of NiOOH and FeOOH, which significantly increases the electrochemical surface area and fully exposes the catalytic active sites. At the same time, this integrated construction strategy avoids the problems of uneven distribution of multi-metal components and insufficient interfacial bonding in traditional electrodeposition methods, so that the obtained oxygen evolution electrode can still maintain excellent operating performance under high current density and has good potential for engineering applications. (3) The N-doped structure formed by the in-situ transformation of chromium doping and nitrogen-containing organic ligands synergistically regulates the electronic structure and reaction interface of the catalyst. This not only inhibits the excessive oxidation of Ni sites at high potentials, but also forms a chlorine-repellent protective layer, reducing the Cl- concentration. - Adsorption and oxidation of Cl effectively alleviate Cl - The corrosion effect on the anode significantly improves the long-term operational stability of the electrode in the seawater electrochemical oxygen desorption reaction. Attached Figure Description
[0021] Figure 1 The X-ray diffraction pattern of the material obtained in Example 1 is shown.
[0022] Figure 2 The image shows the Raman evolution spectrum of the material obtained in Example 1.
[0023] Figure 3 The images shown are scanning electron microscope (SEM) images and elemental distribution maps of the material obtained in Example 1.
[0024] Figure 4 The electrochemical oxidation reaction voltage-current curves of the materials obtained in Example 1 and Comparative Examples 1-3 were obtained by linear sweep voltammetry.
[0025] Figure 5 The image shows the Tafel slope diagram of the electrochemical oxidation reaction of the materials obtained in Example 1 and Comparative Examples 1-3.
[0026] Figure 6 The ratio of chromium ion dissolution to retention after electrochemical testing of the materials obtained in Example 1 and Comparative Example 3.
[0027] Figure 7 This is a stability test graph for Example 1. Detailed Implementation
[0028] The technical solution of the present invention will be illustrated below with specific embodiments, but the scope of protection of the present invention is not limited thereto.
[0029] Electrochemical measurements were performed in a standard three-electrode system controlled by an electrochemical workstation (AMETEK Princeton Applied Research MC). 1 M KOH alkaline seawater (pH ≈ 13.6, NaCl concentration approximately 0.5 M) was used as the electrolyte. The prepared electrode served as the working electrode, while a platinum mesh and a saturated calomel electrode served as the counter and reference electrodes, respectively. All test data were compensated for 85% iR. The recorded current density was 100 mA·cm⁻¹. -2 Overpotential (η) 100 The chromium retention was calculated using ICP testing of the electrodes after electrolysis. Specifically, electrode samples before and after the electrochemical reaction were digested in nitric acid for 12 h to allow the metal elements to fully dissolve before ICP testing. The chromium dissolution rate was calculated as 1 - (chromium ion content after reaction measured by ICP / chromium ion content before reaction measured by ICP) × 100%.
[0030] Example 1 (NiFeCr-MOF / NF) (1) Commercial nickel foam (NF) was selected as the conductive substrate and cut into 1cm×3cm size. It was then placed in acetone and 3M hydrochloric acid solution for ultrasonic cleaning for 3 min each to remove surface oil and oxide layer. Subsequently, it was ultrasonically cleaned in deionized water and anhydrous ethanol for 3 min each to remove residual acid and organic solvent. The treated nickel foam was dried at 60℃ and sealed under vacuum for later use.
[0031] (2) Weigh 1163 mg of nickel nitrate hexahydrate, 808 mg of ferric nitrate nonahydrate and 400 mg of chromium nitrate nonahydrate (Ni:Fe:Cr molar ratio of 2:1:0.5) and dissolve them in 50 mL of N,N-dimethylformamide. Add 1758 mg of 2,2'-bipyridine-5,5'-dicarboxylic acid to the solution and stir thoroughly to form a homogeneous precursor solution. The molar ratio of metal ions, nitrogen-containing organic ligands and organic solvents is 1:1.0:20-200.
[0032] (3) The precursor solution was transferred to a polytetrafluoroethylene-lined reactor. The pretreated nickel foam was vertically immersed into the solution and subjected to a solvothermal reaction at 140°C for 12 h. After the reaction was completed, the electrode was removed, washed with DMF and ethanol, and dried to obtain the NiFeCr-MOF / NF precursor electrode.
[0033] (4) The NiFeCr-MOF / NF precursor electrode was sealed with epoxy resin to fix the active area to 1cm×1cm, and placed in 1 M KOH electrolyte as the anode. A constant anolyte current density of 100 mA·cm was maintained. -2 Electrochemical activation was performed for 12 hours under the specified conditions to finally obtain the NiFeCr-MOF / NF oxygen evolution electrode, denoted as NiFeCr-MOF / NF.
[0034] Comparative Example 1 (NiFe-MOF / NF) The difference from Example 1 is that no chromium source (chromium nitrate nonahydrate) was added.
[0035] Examples 2-9
[0036] The difference from Example 1 is that the molar ratio of nickel, iron, and chromium ions added in Examples 2-9 is different, as shown in Table 1, and the current density is 100 mA·cm. -2 OER overpotential (η) 100 The α and β slopes were obtained by three-electrode electrochemical testing.
[0037] Table 1 Effect of Ni:Fe:Cr molar ratio on OER activity of NiFeCr-MOF / NF electrode
[0038] Table 1 shows that the Ni / Fe / Cr molar ratio significantly affects the oxygen evolution reaction (OER) performance of the electrode in a 1 M KOH alkaline seawater system. Comparative Example 1, without chromium, exhibits the highest overpotential and the largest Tafel slope, indicating slow reaction kinetics. However, with the introduction of chromium, both the overpotential and Tafel slope decrease significantly. Example 1 shows the best performance, indicating that appropriate chromium doping can effectively optimize the electronic structure of the NiFe-based catalyst and accelerate reaction kinetics. When the chromium content further increases (≥0.7%), both the overpotential and Tafel slope rebound, indicating that excessive chromium dilutes the effective active sites of NiFe, deteriorates reaction kinetics, and is therefore unfavorable for the OER, suggesting an optimal doping range for chromium. Furthermore, at the same chromium content, Ni and Fe exhibit a synergistic effect, and excessively high nickel content also leads to poorer electrochemical performance.
[0039] like Figure 1The X-ray diffraction pattern of the NiFeCr-MOF / NF electrode prepared in Example 1 is shown. The results indicate that the diffraction peaks obtained in Example 1 mainly originate from the nickel foam substrate, NiFe-LDH, active NiOOH, and FeOOH. The characteristic diffraction peaks of the activated electrode are relatively broad, indicating that the catalyst underwent in-situ self-reconstruction, generating more amorphous phases. Characteristic diffraction peaks of NiFe-LDH (JCPDS No. 40-0215) can also be observed. Slight negative shifts are observed at angles of 11.4° and 22.9° corresponding to the (003) and (006) crystal planes, indicating that the introduction of chromium and anions leads to increased interlayer spacing and lattice expansion. Furthermore, characteristic diffraction peaks of the active species NiOOH and FeOOH appear at approximately 35.5°, 37.3°, and 66.7° of the activated electrode, indicating that NiFeCr-MOF / NF is transformed into the OER active phase under the reaction conditions.
[0040] like Figure 2 The image shows the Raman evolution spectra of the NiFeCr-MOF / NF precursor electrode electroactivation process (with different electroactivation times) in Example 1. As the electrochemical activation time increases, the electrode initially located at approximately 490 / 564 cm⁻¹... -1 The paired Raman bands gradually shift towards lower wavenumbers, which can be attributed to the formation of β-NiOOH active species. Simultaneously, a band located at approximately 680 cm⁻¹... -1 The spectral band shift to higher wavenumbers can be attributed to the formation of FeOOH active species. Simultaneously, a band located at ~840 cm⁻¹ appears... -1 The Raman characteristic peaks correspond to CrO4 2- The formation of species indicates that Cr undergoes surface reconstruction and forms stable chromate species under strongly alkaline conditions (pH≈14). Combined XRD and Raman analyses show that during OER activation, the NiFeCr-MOF / NF electrode undergoes in-situ transformation from the NiFeCr-MOF precursor to an oxygen-evolving active phase dominated by NiOOH, with FeOOH and CrO4 forming on its surface. 2- The species provide important structural basis for its excellent oxygen evolution activity and seawater corrosion resistance.
[0041] like Figure 3The image shows a scanning electron microscope (SEM) image and elemental analysis diagram of the NiFeCr-MOF / NF electrode prepared in Example 1. The results show that the NiFeCr-MOF / NF electrode forms a continuously covering porous catalyst layer on the surface of the nickel foam substrate, exhibiting a rough surface morphology composed of stacked nanostructure units, which is beneficial for electrolyte penetration and full exposure of active sites. Energy dispersive X-ray spectroscopy (EDS) elemental analysis results show that Ni, Fe, Cr, and N elements are uniformly distributed throughout the catalyst layer, without obvious element enrichment or phase separation, confirming that Cr has been successfully introduced and stably exists in the NiFe-based framework, and that nitrogen-containing ligands have been in situ converted into N elements and doped into the catalyst framework. Elemental doping constructs a multi-level nanostructure with higher structural disorder and larger specific surface area, providing a favorable structural basis for improving the electrode's oxygen evolution activity and seawater corrosion resistance.
[0042] like Figure 7 The figure shown is a stability test graph obtained by the constant current method in the electrolyte for the electrode prepared in Example 1. The current value used in the test was 500 mA·cm. -2 Test results show that this electrode can operate at 500 mA·cm⁻¹. -2 The electrode has been able to operate stably for more than 4,500 hours under high current density, indicating that it has excellent stability in alkaline seawater electrolyte.
[0043] Comparative Example 2 (Unactivated NiFeCr-MOF / NF) The difference from Example 1 is that no electrochemical activation was performed.
[0044] Comparative Example 3 (Electrodeposition of NiFeCr / NF) The difference from Example 1 is that it was prepared by a conventional electrodeposition method.
[0045] (1) Commercially available nickel foam (NF) was selected as the conductive substrate and cut to a size of 1cm × 3cm. The nickel foam was ultrasonically cleaned in acetone and 3M hydrochloric acid solution for 3 min each to remove surface oil and oxide layer; then ultrasonically cleaned in deionized water and anhydrous ethanol for 3 min each to remove residual acid and organic solvent. The treated nickel foam was dried at 60 ℃ and sealed under vacuum for later use.
[0046] (2) Weigh nickel nitrate, iron nitrate and chromium nitrate, and prepare 150 mL of mixed aqueous solution with molar concentrations of 16 mM Ni(NO3)2, 8 mM Fe(NO3)3 and 4 mM Cr(NO3)3 respectively. Stir for 10 min under magnetic stirring to obtain a homogeneous precursor solution.
[0047] (3) Electrodeposition reaction was carried out in a standard three-electrode system, with treated nickel foam as the working electrode, a platinum mesh as the counter electrode, and a saturated calomel electrode (SCE) as the reference electrode. The working electrode was immersed in the above precursor solution, and electrodeposition was carried out under a constant potential of -0.9 V (vs. SCE). The charge reached -20 C, and a NiFeCr layered double hydroxide catalyst layer was generated in situ on the surface of the nickel foam, which was denoted as electrodeposited NiFeCr / NF.
[0048] Table 2 Effect of different preparation methods on OER activity
[0049] like Figure 4 The figure shows the electrochemical oxidation reaction voltage-current curves obtained by linear sweep voltammetry for the materials obtained in Example 1 and Comparative Examples 1-3. The overpotential η can be obtained from the figure. 100 Before testing, the working electrode was subjected to approximately 20 cycles of cyclic voltammetry scans to obtain a stable state, followed by testing at 1 mV·s within the potential range of 1.3–1.7 V (vs. RHE). -1 Linear scan voltammetry was performed at the scan rate.
[0050] As shown in Table 2, the electrode prepared in Example 1 at 100 mA·cm -2 The required overpotential at the current density is only 267 mV, significantly lower than that of NiFe-MOF / NF in Comparative Example 1 (315 mV), unactivated NiFeCr-MOF / NF in Comparative Example 2 (284 mV), and electrodeposited NiFeCr / NF in Comparative Example 3 (294 mV). Meanwhile, as... Figure 5 The selection shown is 10-100 mA / cm. 2 The Tafel slope was calculated regionally, and Example 1 showed the lowest Tafel slope (43.9 mV·dec). -1 The results indicate that it possesses faster reaction kinetics. These results demonstrate that introducing chromium doping and nitrogen-containing ligand-derived structures into NiFe-based catalysts through a combination of in-situ MOF precursor growth and electrochemical self-reconstruction can significantly enhance the OER activity and kinetic performance of NiFe-based electrodes in alkaline seawater environments.
[0051] like Figure 6The figure shows a comparison of the chromium ion dissolution and retention ratios before and after the OER electrochemical reaction in Example 1 and Comparative Example 3. In Comparative Example 3 (electrodeposited NiFeCr / NF), the chromium dissolution rate reached as high as 88%, with a retention ratio of only 12%. In contrast, Example 1 (NiFeCr-MOF / NF) exhibited significantly better chromium stability under strongly alkaline, high-chlorine environments and high anodic potentials, with a chromium dissolution rate of only 61%, indicating that the MOF-derived structure can effectively alleviate excessive chromium dissolution during the OER process. This difference can be attributed to the stable framework structure and more uniform chromium doping state constructed by the synergistic multi-metal nodes in NiFeCr-MOF / NF, which helps enhance the coordination stability and structural constraint of chromium in the catalyst, thereby improving the long-term stability of the electrode under alkaline seawater OER conditions.
[0052] Comparative Examples 4-6 The difference from Example 1 is that, as shown in Table 3, the organic ligands used in Comparative Examples 4-6 are different; Comparative Example 4 uses terephthalic acid ligand, Comparative Example 5 uses 2,5-pyridinedicarboxylic acid ligand, and Comparative Example 6 uses 2-cyanoterephthalic acid ligand.
[0053] Table 3 Effect of different organic ligands on catalyst activity
[0054] Table 3 shows that the type of organic ligand has a significant impact on the oxygen evolution reaction performance and Cr stability of the NiFeCr-MOF / NF electrode in alkaline seawater systems. Example 1, which uses the nitrogen-containing polydentate ligand 2,2'-bipyridine-5,5'-dicarboxylic acid, exhibits the best performance at 100 mA·cm⁻¹. -2The overpotential was only 267 mV, and the chromium dissolution rate was the lowest (61%), indicating that this ligand can form a stable chelate structure with chromium ions through N,O polydentate coordination, thereby effectively inhibiting the dissolution of chromium in the electrochemical process and optimizing the electronic structure and reaction kinetics of the catalyst. In contrast, Comparative Example 4 (terephthalic acid ligand), which does not contain nitrogen ligands, showed a higher overpotential (308 mV) and the highest chromium dissolution rate (91%), indicating that relying solely on carboxyl coordination is insufficient to effectively fix chromium ions, and demonstrating that nitrogen doping has a significant effect on improving activity. Although Comparative Example 5 (2,5-pyridinedicarboxylic acid ligand) contains nitrogen atoms, due to the limited spatial configuration of its coordination sites, it is difficult to form a stable polydentate chelate structure. Its electrocatalytic performance and chromium stability are between those of Example 1 and Comparative Example 4, with a higher chromium dissolution rate (80%). Furthermore, although Comparative Example 6 (2-cyanoterephthalic acid ligand) contains nitrogen, the nitrogen atom in its -CN group is sp hybridized, and the lone pair electrons participate in the π conjugated system, making it difficult to form an effective coordinate bond with chromium ions. Therefore, its Cr dissolution rate (88%) and overpotential (299 mV) are close to those of the nitrogen-free ligand system, indicating that this type of nitrogen-containing ligand does not have an effective chromium ion fixation ability.
[0055] In summary, nitrogen doping has a significant effect on improving catalyst performance. However, not all nitrogen-containing ligands can achieve stable fixation of Cr. Nitrogen-containing polydentate ligands with suitable spatial configurations and multiple coordination sites can form stable Cr chelate structures, thereby significantly improving catalytic activity and anti-dissolution ability. This shows that the present invention has clear structural specificity and significant technical effects in ligand selection.
[0056] Examples 10-14
[0057] The difference from Example 1 is that, as shown in Table 4, the amount of nitrogen-containing ligand 2,2'-bipyridine-5,5'-dicarboxylic acid added to the electrodes prepared in Examples 10-14 is different, resulting in the preparation of NiFeCr-MOF / NF electrodes with different nitrogen-containing ligand ratios.
[0058] Table 4 Effect of nitrogen-containing ligand ratio on electrode OER performance
[0059] Table 4 shows that the amount of nitrogen-containing ligands added significantly affects the oxygen evolution reaction performance and Cr stability of the NiFeCr-MOF / NF electrode in alkaline seawater. When the amount of ligands is low (Example 10), the number of nitrogen sites that can participate in coordination in the system is insufficient, making it difficult to form a sufficient Cr-N coordination structure, resulting in weak Cr fixation capacity and high overpotential, indicating poor catalytic activity. With the increase of ligand amount (Examples 1, 11, 12, 13), the Cr fixation capacity improves, indicating that a more sufficient multidentate coordination structure is formed in the system, effectively inhibiting Cr dissolution and optimizing the electronic structure of the catalyst. Among them, Example 1 shows the best performance, at 100 mA·cm⁻¹. -2 The lowest overpotential (267 mV) and the smallest Tafel slope (43.9 mV·dec) were observed. -1 This indicates optimal reaction kinetics. When the ligands are further in excess (Example 14), the electrode performance shows a downward trend, and the overpotential increases significantly. This is mainly because the excess organic ligands reduce the exposure of active sites and the conductivity of the material. At the same time, excessive coordination may inhibit the electronic regulation of Ni / Fe active sites, which is not conducive to the oxygen evolution reaction.
[0060] In summary, there is an optimal range for the amount of nitrogen-containing ligands introduced. Within an appropriate range, increasing the amount of ligand helps to enhance Cr-N coordination and improve catalytic activity; however, when the amount of ligand is too low or too high, it leads to a decrease in catalytic performance, indicating that the level of N doping has a synergistic regulatory effect on the activity and stability of the catalyst.
[0061] The above are merely preferred embodiments of the present invention and do not limit the patent scope of the present invention. Any equivalent structural or procedural transformations made using the present invention specification, or direct or indirect applications in other related technical fields, are similarly included within the patent protection scope of the present invention.
Claims
1. A method for preparing a NiFeCr oxygen evolution electrode based on nitrogen-containing organic ligand chelation, characterized in that, Includes the following steps: (1) A precursor solution is obtained by dissolving a nickel source, an iron source, a chromium source and a nitrogen-containing organic ligand in an organic solvent; the nitrogen-containing organic ligand is one or more of 2,2'-bipyridine-5,5'-dicarboxylic acid, 2,2'-bipyridine-4,4'-dicarboxylic acid, 2,5-pyridinedicarboxylic acid, tetracarboxyphenylporphyrin and 3,5-pyrazoledicarboxylic acid; the molar ratio of Ni, Fe and Cr in the nickel source, iron source and chromium source is 2-3:1-2:0.3-0.6; the ratio of the total molar amount of metal ions to the molar amount of nitrogen-containing organic ligand in the precursor solution is 1:0.75-1.5; (2) The pretreated conductive substrate is immersed in the precursor solution and subjected to a solvothermal reaction to obtain the NiFeCr-MOF precursor electrode; (3) The NiFeCr-MOF precursor electrode was placed in an alkaline electrolyte for electrochemical activation to obtain an N-doped NiFeCr oxygen evolution electrode.
2. The method for preparing a NiFeCr oxygen evolution electrode based on nitrogen-containing organic ligand chelation according to claim 1, characterized in that, In step (1), the ratio of the total molar amount of metal ions to the molar amount of organic solvent in the precursor solution is 1:20-200.
3. The method for preparing a NiFeCr oxygen evolution electrode based on nitrogen-containing organic ligand chelation according to claim 1, characterized in that, In step (1), the nickel source, iron source and chromium source are one or more of nitrate, chloride, sulfate and acetate, respectively.
4. The method for preparing a NiFeCr oxygen evolution electrode based on nitrogen-containing organic ligand chelation according to claim 1 or 3, characterized in that, In step (1), the organic solvent is one or more of N,N-dimethylformamide, N,N-dimethylacetamide, ethanol, methanol, isopropanol, dichloromethane, acetonitrile and dimethyl sulfoxide.
5. The method for preparing a NiFeCr oxygen evolution electrode based on nitrogen-containing organic ligand chelation according to claim 1, characterized in that, In step (2), the conductive substrate includes carbon paper, carbon cloth or nickel foam.
6. The method for preparing a NiFeCr oxygen evolution electrode based on nitrogen-containing organic ligand chelation according to claim 1 or 5, characterized in that, In step (2), the pretreatment of the conductive substrate includes the following steps: the conductive substrate is ultrasonically cleaned sequentially with organic solvent and acidic solution, then cleaned with water and alcohol solvent and dried to obtain the pretreated conductive substrate.
7. The method for preparing a NiFeCr oxygen evolution electrode based on nitrogen-containing organic ligand chelation according to claim 1, characterized in that, In step (2), the solvothermal reaction is carried out at 100-160℃ for 6-24 h.
8. The method for preparing a NiFeCr oxygen evolution electrode based on nitrogen-containing organic ligand chelation according to claim 1 or 7, characterized in that, In step (3), the alkaline electrolyte is a 0.5-3 M KOH solution; the electrochemical activation is performed at a constant current density of 10-300 mA•cm. -2 Activation time is 2-24 hours.
9. The application of a NiFeCr oxygen evolution electrode prepared by any one of claims 1-8 in the electrolytic oxygen evolution reaction of seawater.
Citation Information
Patent Citations
Monatomic nickel-nitrogen coordination co-doped porous carbon / nano-zirconia composite electrode as well as preparation method and application thereof
CN113430554A
Method for preparing transition metal-based electrocatalytic water decomposition anode catalytic material and application of transition metal-based electrocatalytic water decomposition anode catalytic material
CN118186400A
